A fair share? Animal health actors and resources in One Health initiatives: A multisite case study in Ethiopia and Pakistan - Dorien H. Braam; Alex Tasker; Ellie Parravani; Klara Saville (CABI, 2023)
Abstract Increased outbreaks of zoonotic diseases with pandemic potential and the growing threat of antimicrobial resistance have stimulated the uptake and use of One Health approaches across the globe. Collaborative, multisectoral, and transdisciplinary approaches are vital to the effective response to health challenges; however, within One Health initiatives, animal and environmental health voices often remain secondary to human health. This article presents the findings of a transdisciplinary research project investigating the roles and contributions of animal health in One Health initiatives. We combined a multisite case study approach with a literature review, and conducted 22 semi-structured key informant interviews with animal health and One Health experts, with a focus on Ethiopia and Pakistan. Key themes explored were the nature of the animal health sector, animal health workforce, veterinary medicines and vaccines, and coordination and collaboration. Results were triangulated with existing primary and secondary data, reviewed by key stakeholders in Ethiopia and Pakistan, and tested with members of the Action for Animal Health (A4AH) coalition. We found that while One Health has become more interdisciplinary and inclusive at a global level, there remain significant challenges in operationalizing the approach at national and subnational levels. Gaps in governance, political will, and capacity undermine the inclusion of animal health in One Health structures. Power and resources are distributed unequally across One Health coalitions, echoing observations that acknowledge the crucial role of communities in supporting the provision of essential services, while their knowledge and experiences often remain excluded from project and policy development. We conclude that stronger multilevel linkages and engagement between animal health and other sectors are vital to support the implementation of inclusive, well-resourced, and effective One Health approaches.